Transplantasi Stem Cell untuk Keganasan Hematologi - Desi Oktariana; Legiran Legiran; Phey Liana; Kemas Y. Rahadiyanto; Gita D. Prasasty; Evi Lusiana; Nia S. Tamzil (eJournal Kedokteran Indonesia, 2022)
Insiden keganasan hematologi terus bertambah serta memiliki tingkat morbiditas dan mortalitas yang tinggi. Keganasan hematologi adalah kondisi sel-sel hematologi seperti eritrosit, leukosit, dan trombosit, tumbuh tidak terkendali dan tidak mengalami kematian sehingga mendominasi populasinya dan tidak dapat berfungsi normal. Terapi stem cell pada keganasan hematologi yang disebut juga terapi transplantasi sumsum tulang, merupakan modalitas terapi utama untuk gangguan hematologi dan keganasan yang memungkinkan pemulihan komponen seluler darah, termasuk monosit, limfosit, basofil, eosinofil, neutrofil, eritrosit, dan trombosit. Stem cell yang dapat digunakan pada keganasan hematologi adalah kombinasi hematopoietic stem cell (HSC) dan mesenchymal stem cells (MSC) untuk transplantasi sumsum tulang dan pemulihan kekebalan untuk gangguan hematologi. Penggunaan HSC dengan ko-terapi MSC dapat memfasilitasi kelangsungan hidup cangkok dari transplantasi HSC. Kata kunci: keganasan, hematologi, stem cell.   Stem Cell Transplantation for Hematology Malignancy Abstract The incidence of hematological malignancies continues to increase and has a high rate of morbidity and mortality. Hematological malignancies are conditions of hematological cells such as erythrocytes, leukocytes, and platelets, growing uncontrollably and not dying so that they dominate the population and cannot work normally. Stem cell therapy in hematological malignancies, also known as bone marrow transplantation therapy, is the main therapeutic modality for hematological disorders and malignancies that supports the restoration of cellular components of blood, including monocytes, lymphocytes, basophils, eosinophils, neutrophils, erythrocytes, and platelets. Stem cells that can be used in hematological malignancies are a combination of hematopoietic stem cells (HSC) and mesenchymal stem cells (MSC) for bone marrow transplantation and immune restoration for hematological disorders. The use of HSCs with MSC co-therapy can help revive grafts from HSC transplants. Key words: malignancy, hematology, stem cell.